Traveling With Integrity: Translating Face‐to‐Face Teacher Professional Learning to Online and Blended Spaces. Issue 2 (28th August 2019) - Katz, Mira‐Lisa; Stump, Mary; Charney‐Sirott, Irisa; Howlett, Heather
Abstract: This department focuses on literacy leaders, including school and instructional leaders, teachers, and external partners, who are working to improve outcomes for adolescent and adult learners in a wide range of education settings. Columns investigate the challenges and complexities inherent in such work and share lessons learned, impactful strategies and approaches, and promising pathways forward.